Objection hearing on property assessment rate charges in Malaysia. - Muhammad, Sani Habibu; Ishak, Mohd Bakri (IISTE, 2013)
The Local Authority Act 171 of 1976 intended fairness by incorporating provisions for seeking redress by property owners who are not satisfied with rates imposed on them based on the assessed value of their properties. This redress is sought by means of filing objections to the local authority concerned, it is then studied and a fair hearing given to the appellant before a decision is taken. The study was conducted, using a semi structuredinterview guide by interviewing the valuation officers about the various reasons for objections, Documents were sought to study past reasons filed by appellants and later triangulated with observation during hearing sessions of the local authorities to a point of saturation. It was found that greater proportion of objections were based on non satisfactory service delivery by the local authorities with only a few on in ability to pay.